2002
DOI: 10.1046/j.1469-0691.2002.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of catheter-related infections with special emphasis on prevention based on educational programs

Abstract: Intra-vascular access is an unavoidable tool in sophisticated modern medical practice, and catheter-related infection remains a leading cause of nosocomial infections, particularly in intensive care units where it is associated with significant patient morbidity, mortality, and additional hospital costs. The incidence of catheter-related bloodstream infection ranges from 2 to 14 episodes per 1000 catheter-days. On average, microbiologically documented, device-related bloodstream infections complicate the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 115 publications
(199 reference statements)
2
64
1
8
Order By: Relevance
“…Catheter tip colonization: absence of infection signs at the catheter insertion site and microorganisms growth ≥ 10 3 UFC/ mL (by quantitative culture) or ≥ 15 UFC/ mL (by semiquantitative culture) [9].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter tip colonization: absence of infection signs at the catheter insertion site and microorganisms growth ≥ 10 3 UFC/ mL (by quantitative culture) or ≥ 15 UFC/ mL (by semiquantitative culture) [9].…”
Section: Definitionsmentioning
confidence: 99%
“…www.bjid.com.br Catheter associated infection: positive hemoculture with the same microorganism which is present on the catheter tip (by either quantitative or semi-quantitative culture) and clinical and microbiological absence of any other source of infection [9].…”
Section: Definitionsmentioning
confidence: 99%
“…12% of all nosocomial infections reported in a study on more than 10,000 European intensive care patients) [24], and are associated with significant attributable mortality (4 to 30%) and costs (USD 4,000 to USD 40,000) [25]. More than 85% of primary nosocomial bacteremias are intravascular catheterrelated [25] and it has been shown that the mortality rate attributed to catheter-related S. aureus bacteremia (8.2%) significantly exceeds the rates for other pathogens [26]. These aspects are particularly relevant to hospitalized IDUs, because most of them need a vascular access, frequently a central venous catheter, since peripheral line insertion and even blood drawings are often difficult or impossible in IDUs.…”
Section: Nosocomial S Aureus Infections and Idusmentioning
confidence: 99%
“…Several preventive measures regarding skin disinfection, sterile insertion, dressing, handling and replacement of the catheter have been shown to reduce the incidence of CRBSI and have been recommended [25,28].As a result of the implementation of these measures, during the last 10 years the incidence of intravascular device-associated bloodstream infections has decreased in the United States by nearly 40% [29]. Educational programs also proved to be very effective in reducing rates of CRBSI [30,31].…”
Section: Nosocomial S Aureus Infections and Idusmentioning
confidence: 99%
“…The condition shows high frequency, representing for instance 12% of all nosocomial infections in an European study involving over 10,000 Intensive Care Unit (ICU) patients [4] . It is also related to significant mortality rates (4a 30%) [5] .…”
Section: Introductionmentioning
confidence: 99%